2001
DOI: 10.1111/j.1151-2916.2001.tb01003.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Neutron Powder Diffraction Study of Ti3SiC2 Synthesis

Abstract: The synthesis of Ti3SiC2 by pressureless reactive sintering of Ti/SiC/C mixtures under an Ar atmosphere has been studied using in situ neutron diffraction. The intermediate phases TiCx and Ti5Si3Cx (x≤ 1) form first at ∼800–1400°C. These phases are consumed in the formation of Ti3SiC2, at ∼1500°C. After sintering, Ti5Si3Cx disappears but an amount of TiCx remains in the sample primarily as a surface layer. The studies appear to support a suggestion that the intermediate phases react to form Ti3SiC2 through a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 25 publications
6
50
0
2
Order By: Relevance
“…Racault et al [29] were first to observe the decomposition of Ti 3 SiC 2 into TiC x and gaseous Si, which has been confirmed by others [13,20,30]. Racault [13] reported that this reaction was promoted by the presence of carbon.…”
Section: Introductionmentioning
confidence: 71%
“…Racault et al [29] were first to observe the decomposition of Ti 3 SiC 2 into TiC x and gaseous Si, which has been confirmed by others [13,20,30]. Racault [13] reported that this reaction was promoted by the presence of carbon.…”
Section: Introductionmentioning
confidence: 71%
“…[1][2][3][4][5] Ti 3 SiC 2 is most often prepared from starting powder mixtures including pure titanium, such as Ti/Si/C [6][7][8][9][10][11] , Ti/C/SiC 2,12-15 and Ti/Si/TiC [16][17][18] by use of different powder metallurgical synthesis methods, e.g. hot pressing, 2,8,10 hot isostatic pressing, 12,17 vacuum sintering, 7,11,15,18 pressureless sintering, 6,9,13,14,16 mechanical alloying [19][20][21] and self-propagation high-temperature synthesis. 22 Pure titanium powder is highly oxidizing and thus has to be handled with great care under strict safety precautions.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 13 who observed that the presence of titanium carbide in the sample was deleterious to the thermochemical stability of Ti 3 SiC 2 . Gao et al 17 stated that the stability was related to the vapor pressure of silicon in the furnace.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion-controlled solid state reaction of Ti 3 SiC 2 is known to require sufficient time at elevated temperatures. 24 The transition zone, region II, does probably not completely melt during the evaporation process since the observed layered regions resembles the virgin Ti 3 SiC 2 grains in terms of size and shape. Instead, region II is exposed to high temperature spikes during and right after the discharge due to inward heat conductions from the surface.…”
Section: Discussionmentioning
confidence: 99%